Upper Limb Ischemia Due to Arterial Thrombosis after COVID-19 Vaccination - Moaath M. Alsmady; Rahaf A. Al-Qaryouti; Nesrin G. Sultan; Oweis I. Khrais; Huthaifah Khrais (Case Reports in Medicine)
This report describes a case of a 60-year-old male patient who received the first dose of the AstraZeneca vaccine and presented to the emergency department complaining of left hand pain and paresthesia. Investigations revealed upper limb ischemia; he was hospitalized for further management.